O futuro dos precedentes judiciais no sistema jurídico brasileiro com enfoque na admissibilidade recursal - Tedeschi, Thiago Conte Lofredo (2015)
This work deals with the study of the surrounding factors in judicial precedents, analyzing the facts, consequences and evolution of the legal system and its application in present days. Brings the history of the systems used in the legal sphere, analyzing the behavior and evolution of each society and its regime adopted, drawing a parallel between the commom law and civil law systems. Aims to demonstrate concepts in the field of trends and effects of each system, exposing the real consequences and possible problems to be generated in the legal field. Presents a study of standardization of Brazilian law according to the evolution accompanying the society, the risk that the system may provide and the benefits generated to the collective from a clear idea of stability and legal certainty. Draws a parallel between the right and the very essence of the idea intended to characterize the foregoing, inserting them in systems of ideas in the world; civil law and common law. And exposes points as repetitive questions of search resources of an improvement in the applicability of everyday issues in society today. Aims to cover all the topics and points presented above, concluding for the evolution that is required of the science of law, in the manner in which they must evolve coming the closest to the assertiveness of an effective, modern and secure system